2013
DOI: 10.2196/mhealth.2432
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Engagement With a Mobile Self-Management System for People With Type 2 Diabetes

Abstract: BackgroundIn a growing number of intervention studies, mobile phones are used to support self-management of people with Type 2 diabetes mellitus (T2DM). However, it is difficult to establish knowledge about factors associated with intervention effects, due to considerable differences in research designs and outcome measures as well as a lack of detailed information about participants’ engagement with the intervention tool.ObjectiveTo contribute toward accumulating knowledge about factors associated with usage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 67 publications
5
58
0
Order By: Relevance
“…22,23 Many users report achieving mastery of self-management content described within prior apps. 22 Others report feeling burdened by intrusive alerts, repetitive content, or faulty technical features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Many users report achieving mastery of self-management content described within prior apps. 22 Others report feeling burdened by intrusive alerts, repetitive content, or faulty technical features.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Many users report achieving mastery of self-management content described within prior apps. 22 Others report feeling burdened by intrusive alerts, repetitive content, or faulty technical features. 22 Decreasing user engagement due to mastery of the app content is less concerning, and likely translates into an enduring improvement in asthma knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In our formative research, 18 some individuals predicted that they would use the mobile app to learn sun protection and then discontinue use, a trend observed with a diabetes self-management mobile app. 41 Some participants also may have tried Solar Cell and felt they already knew its advice. Increased use of Solar Cell was associated with improvements in sun protection practices and less time spent in the midday sun, so, future research on implementation strategies for mobile interventions is an important consideration both in randomized trials and when evidence-based interventions are translated more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers indicated that most of the users followed an intermittent continuance pattern in the long-term usage of activity tracker [4], and users were accustomed to taking short breaks when using health wearables [5]. Moreover, in terms of smart health devices with specific functions, such as mobile self-management system for people with diabetes, users were prone to gradually decrease their usage frequency, instead of completely continuance or discontinuance usage [7].…”
Section: Post-adoptive Usage Behavior Of Smart Health Devicesmentioning
confidence: 99%